MONITORING PENCEGAHAN STUNTING MELALUI E-POSYANDU DI YOGYAKARTA - Dewi, Riskha Dora Candra (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The prevalence of stunted toddlers in Yogyakarta in 2019 was 10.69%. To encourage this reduction in stunting rates, the DIY government uses the electronic posyandu application (e-Posyandu) as a tool for monitoring infant health. This study aims to describe the monitoring of stunting prevention through e-Posyandu in Yogyakarta. This study used a qualitative descriptive research design. The results of the study show that e-Posyandu is a tool for cadres or health workers to provide maximum service to the community, especially mothers and children. Through e-Posyandu, parents can also ascertain the closest posyandu location, schedule and type of immunization that has been carried out so that parents can estimate the schedule of posyandu visits next